Robot-Assisted Magnetic Resonance Imaging-Targeted versus Systematic Prostate Biopsy; Systematic Review and Meta-Analysis - Petov, Vladislav; Azilgareeva, Camilla; Shpikina, Anastasia; Morozov, Andrey; Krupinov, German; Kozlov, Vasiliy; Singla, Nirmish; Gómez Rivas, Juan; Jesús, Moreno-Sierra; Puliatti, Stefano; Checcucci, Enrico; Rodler, Severin; et al. (Cancers, 2023)
Introduction: Robot-assisted devices have been recently developed for use in prostate biopsy. However, it is possible advantages over standard biopsy remain unclear. We aimed to assess the diagnostic performance and safety of robot-assisted targeted (RA-TB) and systematic prostate biopsies (RA-SB). Methods: A systematic literature search was performed in MEDLINE and Scopus databases. The detailed search strategy is available at Prospero (CRD42021269290). The primary outcome was the clinically significant prostate cancer (PCa) detection rate. The secondary outcomes included the overall detection rate of PCa, cancer detection rate per core, and complications. Results: The clinically significant cancer detection rate, overall cancer detection rate, and “per patient” did not significantly differ between RA-TB and RA-SB [OR = 1.02 (95% CI 0.83; 1.26), p = 0.05, I2 = 62% and OR = 0.95 (95% CI 0.78; 1.17), p = 0.17, I2 = 40%, respectively]. There were no differences in the clinically insignificant cancer detection rate “per patient” between RA-TB and RA-SB [OR = 0.81 (95% CI 0.54; 1.21), p = 0.31, I2 = 0%]. RA-TB had a significantly higher cancer detection rate “per core” [OR = 3.01 (95% CI 2.77; 3.27), p < 0.0001, I2 = 96%]. Conclusion: RA-TB and RA-SB are both technically feasible and have comparable clinical significance and overall PCa detection rates.
Gesehen am 01.10.2024